Effect of amino acids in the stability study of hydrolase enzymes produced via solid-state fermentation using empty fruit bunch and palm oil mill sludge - F. H., Zainuddin; Ling, K. M. T.; N. H., Abdul Mutallib; N.S ., Azizul Shahizani; Noraziah, Abu Yazid (Elsevier Ltd, 2024)
Solid-state fermentation (SSF) is an alternative treatment for valorizing agro-waste, as well as broadening their potential uses in the production of industrial enzymes. This study aims to investigate an addition of amino acids affecting the stability of hydrolases enzymes produced from SSF. The SSF was carried out for nine days with and without the addition of amino acids as a booster. About 16–57 % increased yield in the hydrolytic enzymes were obtained in the SSF with amino acids when compared to the SSF without. The yields of the enzymes remained high in the SSF with amino acids over the wide range of temperature and pH. Hence, the addition of amino acids enhanced the stability and enzymes yield.